OPTIMASI VIDEO STREAMING DARI SERVER KE CLIENT PADA JARINGAN BLUETOOTH PICONET PERVASIVE - Hasad, Andi (JREC (Journal of Electrical and Electronics), 2012)
ABSTRACT The objective of this research is to develop a piconet pervasive system by performing the optimization and analysis of video streaming on the network by utilizing the bluetooth cell phones and computers media in an condition which have Wi-Fi or do not have Wi-Fi. Stages of research include : analysis of bluetooth network system, design a prototype system, audio video compression, hint track, optimization, system testing, performance measurement, and analysis of measurement results. The results obtained from measurements of packet loss value for all video compression on a client-server distance of 10 m has been fulfilling the Cisco standard of QoS video streaming, where the smallest value obtained at 8 kbps data rate of 4.38% packet loss Â to an condition that does not have Wi-Fi, and a distance of client - server 10 m. In condition that have Wi-Fi signal strength of -78 dBm, the smallest value obtained of 4.64% packet loss. Throughput and delay parameters of the video compression meets the QoS of video streaming in which the delay have values ranged from 0.62 - 1.81 milliseconds, while the standard of maximum delay for QoS video streaming is 5 seconds. The results Â showed a video streaming system that meets the Cisco standard for QoS video streaming value of the throughput, delay, jitter and packet loss. Keywords : video streaming, bluetooth, optimization, client-server, piconet pervasive